A Vivid Orange New Genus and Species of Braconid-Mimicking Clearwing Moth (Lepidoptera: Sesiidae) Found Puddling on Plecoptera Exuviae - Marta Skowron Volponi (Insects, 2020)
A clearwing moth with a distinct orange, black and white colour pattern was found sucking up fluids from Plecoptera (stonefly) exuviae on rocks, surrounded by water, on a river bank in Thailand. During this process, known as puddling, the sesiid ejected brown liquid, indicating that it was not imbibing water alone. The behaviour was documented via video recording. Morphological and DNA analyses indicate that the moth is a new genus and species of the tribe Osminiini and it is described herein as Aurantiosphecia piotrii genus et species nova. Two species of Aschistophleps Hampson, 1893 have been transferred to the newly established genus. The barcode sequence of the cytochrome c oxidase I gene was obtained with universal invertebrate primers after two sets of standard Lepidoptera primers failed to generate a product. Sections on behaviour, conditions of occurrence and possible mimicry models are included. The unique colouration and body posture of A. piotrii suggest that it is a braconid wasp mimic, with the mimicry model potentially also being the sesiid’s parasitoid.